Ventricular tachycardia storm as predominant cardiac manifestation of lupus myocarditis - Caryn Tsujean, Lim; Yik Hon, Ho; Ling, Hwei Sung; Keng Tat, Koh; Cheng Lay, Teh; Tiong Kiam, Ong (Medical Journal of Malaysia Case Reports (MJM Case Reports), 2022)
SUMMARY Systemic lupus erythematosus (SLE) is a multi-system autoimmune disease that can affect any part of the heart, causing arrhythmias on top of other cardiac manifestations. Malignant ventricular tachyarrhythmias are rare manifestations of SLE. Our case is the first one reported in the literature of an SLE patient with multi-organ involvement who subsequently presented with ventricular tachycardia (VT) storm as a cardiac manifestation. This case also demonstrates the use of Stellate ganglion block to treat intractable VT storm when chemical and electrical cardioversions failed, while waiting for immunosuppressive drugs to take effect. Timely treatment resulted in a good outcome for our patient.